Intellectual Property - Lakshmana Prabu, Sakthivel; Narasimman Kuppusami Suriyaprakash, Timmakkondu (IntechOpen, 2022)
Intellectual Property discusses issues pertaining to intellectual property rights, specifically patents and patent-related issues. It considers divergent issues related to patents starting from invention to filing of a patent and the issues that come along with it. Written by authors from all over the world, this book discusses such topics as writing and defending patent applications; national and legal rules and policies regarding intellectual property rights; the laws, regulations, rules, and procedures of appeals in major patent offices in Europe and the United States; and more.